Unusual presentation of colon cancer as rectal prolapse in middle‐aged male - Ashley A. Penton; Sarah B. Jochum; Joshua M. Eberhardt (Clinical Case Reports)
Abstract Rectal prolapse is typically a benign idiopathic condition. Rarely, rectal prolapse can be due to or associated with colorectal carcinoma. Here we present a middle‐aged gentleman with no previous medical or surgical history, who presented with rectal prolapse secondary to sigmoid adenocarcinoma.